2012
DOI: 10.1007/8904_2012_180
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone for Alexander’s Disease: A Four-Year Follow-Up

Abstract: In 2010, we reported the successful clinical outcome related to a 20-month course of intravenous, cyclical ceftriaxone, in a patient with adult-onset Alexander's disease. We now provide evidence that the progression of the patient's signs/symptoms was halted and reversed with a 4-year-long extension of the trial.The patient's clinical signs/symptoms were evaluated before the start and every 6 months for 6 years. For the early 2 years, without therapy, and for the following 4 years, after intravenous ceftriaxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, whether these findings can be translated into clinical application is an open question. Pharmacologic approaches have targeted other pathways downstream of mutant GFAP, such as use of ceftriaxone to increase expression of glutamate transporters (Bachetti et al., 2010; Sechi et al., 2013). Based on the evidence described earlier that Alexander disease is associated with reduced expression of Glt-1, increasing its levels could be beneficial.…”
Section: Reliefmentioning
confidence: 99%
“…However, whether these findings can be translated into clinical application is an open question. Pharmacologic approaches have targeted other pathways downstream of mutant GFAP, such as use of ceftriaxone to increase expression of glutamate transporters (Bachetti et al., 2010; Sechi et al., 2013). Based on the evidence described earlier that Alexander disease is associated with reduced expression of Glt-1, increasing its levels could be beneficial.…”
Section: Reliefmentioning
confidence: 99%
“…Lysosomes were also identified in untreated embryos expressing p.R239C, a presence that may be linked to the activation of cellular autophagy, a known cellular response to proteasome overloading caused by mutant GFAP [ 33 ]. These results not only provided further validation of the zebrafish model by reproducing the effects of the drugs observed in cell cultures and in a patient [ 10 , 28 ], but also confirmed that ceftriaxone is worthy of further investigation as therapy.…”
Section: Discussionmentioning
confidence: 63%
“…To further validate the zebrafish model of AxD, we investigated whether the antibiotic ceftriaxone (CEF), previously shown to decrease mutant GFAP aggregation in vitro [ 10 ] and to improve the clinical severity in an AxD patient [ 28 ], could also exert beneficial effects in our in vivo model.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that some compounds used in clinical practice for decades have been demonstrated to pass freely through the BBB and to be effective in the treatment of some neurodegenerative disorders. This is the case for ceftriaxone, a β-lactam antibiotic used for halting or reversing neurodegeneration in some disorders such as Alexander’s Disease and Parkinson's Disease, thanks to its chaperon-like effect on some of the misfolded proteins involved in these pathologies (GFAP and α-synuclein, respectively) [ 125 , 126 , 127 ].…”
Section: Tau Spreading Implications For Dysfunctional Tauopathiesmentioning
confidence: 99%